Creative Destruction and Transition : The Effects of Firm Entry and Exit on Productivity Growth in Estonia - Jaan Masso; Raul Eamets; Kaia Philips (Institute for the Study of Labor (IZA), 2004)
This paper presents one of the first studies of firm demographics in Estonia, particularly, on the processes of firm entry and exit as well as survival analysis of new firms. Also decompositions of productivity change into components consisting of resource reallocation, firm entry and exit, and productivity growth within continuing firms is carried out. Our results, derived from a novel database of the population of Estonian firms, show that firm turnover has been rather high in Estonia during the observed period from 1995 to 2001, resulting from low institutional entry barriers and emergence of the SME sector. The high survival rates for new firms and surviving firms? relatively fast growth could reflect their relatively high productivity compared to incumbent firms and changes in the sectoral structure of the economy. The decomposition of productivity change shows that the high productivity growth has been mostly from within-firm productivity growth (e.g. the adoption of new production technologies and organizational changes), but the reallocation of production factors (especially the exit of low productivity units) has played an important role as well.
Keywords: D24; L11; O30; O12; 330; firm survival; firm entry and exit; productivity decompositions; Estonia; Industrieökonomik; Markteintritt; Marktaustritt; Unternehmensgründung; Unternehmensentwicklung; Produktivität; Schätzung; Estland